If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -10 = -60 + -10x Reorder the terms: -10 + 4x = -60 + -10x Solving -10 + 4x = -60 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. -10 + 4x + 10x = -60 + -10x + 10x Combine like terms: 4x + 10x = 14x -10 + 14x = -60 + -10x + 10x Combine like terms: -10x + 10x = 0 -10 + 14x = -60 + 0 -10 + 14x = -60 Add '10' to each side of the equation. -10 + 10 + 14x = -60 + 10 Combine like terms: -10 + 10 = 0 0 + 14x = -60 + 10 14x = -60 + 10 Combine like terms: -60 + 10 = -50 14x = -50 Divide each side by '14'. x = -3.571428571 Simplifying x = -3.571428571
| 41-5x=14-8x | | x+(x*0.28)=100 | | 10+6x=-15+x | | 3x-9=x+27 | | Ln(x-3)= | | -(-1k+1)=-5(1-6k)+7k | | b+3=3 | | y-9=-17 | | 4.8x+38.3=10.9-8.9x | | 1/3x-5/6=1/9x | | sqrt(2x^2-5x-3)=x+1 | | 15x^2+3x= | | x+sqrt(25-x^2)=7 | | 5y*2y-3= | | x^2+sqrt(25-x^2)=7 | | 2(x+1)+3x+6=4 | | 15x-7=-2 | | t^2+4t+3=0 | | 28=2x+2 | | 3lnx^6-2lnx^2=14 | | 3ln(x^6)-2ln(x^2)=14 | | 3x-9x+5x-7x= | | cos^2x-sen^2x=0 | | 0.025p-2=0.15(p-5) | | 2.1d+18=216(d+8) | | z*8+(3-i)*z*4-3*i=0 | | 5v+3=7 | | 2q-4+8q=yq-8+3q | | 3b-(1-2b)= | | 3.5x+12=5.25x | | lg(5x-2)=lg(2-5x) | | 3b+(1-2b)= |